IMPLEMENTASI SISTEM PEMANTAUAN KUALITAS AIR DENGAN IOT DI PLANT FACTORY KEBUN PERCOBAAN FAKULTAS PERTANIAN UNIVERSITAS UDAYANA - Artha Wiraguna, I Putu A.B.; Setiawan, I Nyoman; Amrita, Anak Agung Ngurah (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i02.p9, 2022)
Plant Factory is a technological concept that forms an ideal environment for plant growth. Water quality has several factors including pH value, water nutrient level (ppm), water temperature and others, plants require a pH value of 5.5 to 6. Differences in pH values and plant nutrients affect plant growth. Lettuce Cultivation has different nutrient requirements for water where plants need around 1000-2000 ppm and 20-25°C in order to produce good growth. Therefore we need a system that can regulate and monitor water quality that can be monitored anywhere. Based on system testing that has been carried out for 30 days, it is found that all components used function as expected, the water quality monitoring sensor is able to detect the value of pH, TDS, water temperature with an average difference with measuring instruments below 2%. After being tested for 30 days from planting to harvesting, the tool can still function properly with indicators that this tool can record data for 30 days and store all data in the database accurately.